The effect of project-based learning on Social Studies learning outcomes - Dika Darmina; Fasrah Indah (Himpunan Pengembang Kurikulum Indonesia, 2026)
Social Studies instruction in junior high schools remains dominated by conventional methods, which contribute to low student engagement and learning outcomes. Therefore, this study was conducted to provide empirical evidence on the implementation and effectiveness of Project-Based Learning (PjBL) in improving student engagement and learning outcomes in Social Studies, to describe its implementation and analyze its influence on student learning outcomes at SMP Muhammadiyah 2 Depok, Sleman. The study used a mixed-method approach with an Exploratory Sequential design. Qualitative subjects included Social Studies teachers, the principal, the vice principal, and four grade VII students, while quantitative subjects consisted of 26 grade VII B students. Data were collected through observation, interviews, documentation, and pretest and posttest, then analyzed qualitatively and quantitatively using n-gain and paired sample t-test. The results showed that PjBL was implemented systematically and effectively to improve Social Studies learning outcomes, indicated by an increase in the average value from 62.50 to 87.12 with an n-gain of 0.6671 and a significance of 0.000 (<0.05). Supporting factors include teacher readiness and student participation, while the main obstacles are time constraints and differences in student abilities. Abstrak Pembelajaran IPS di SMP masih didominasi metode konvensional yang berdampak pada rendahnya keterlibatan dan hasil belajar murid. Oleh karena itu, alasan penelitian ini dilakukan untuk memberikan bukti empiris mengenai implementasi dan efektivitas Project-Based Learning (PjBL) dalam meningkatkan keaktifan dan hasil belajar IPS, dengan tujuan mendeskripsikan pelaksanaan PjBL serta menganalisis pengaruhnya terhadap hasil belajar murid di SMP Muhammadiyah 2 Depok Sleman. Penelitian menggunakan pendekatan mixed-method dengan desain Exploratory Sequential. Subjek kualitatif meliputi guru IPS, kepala sekolah, wakil kepala sekolah, dan empat murid kelas VII, sedangkan subjek kuantitatif terdiri atas 26 murid kelas VII B. Data dikumpulkan melalui observasi, wawancara, dokumentasi, serta tes pretest dan posttest, kemudian dianalisis secara kualitatif dan kuantitatif menggunakan n-gain dan paired sample t-test. Hasil penelitian menunjukkan bahwa PjBL dilaksanakan secara sistematis dan efektif meningkatkan hasil belajar IPS, ditunjukkan oleh peningkatan nilai rata-rata dari 62,50 menjadi 87,12 dengan n-gain 0,6671 dan signifikansi 0,000 (<0,05). Faktor pendukung meliputi kesiapan guru dan partisipasi murid, sedangkan kendala utama adalah keterbatasan waktu dan perbedaan kemampuan murid. Kata Kunci: hasil belajar; Ilmu Pengetahuan Sosial; implementasi PjBL; pembelajaran berbasis masalah